THE MINIMUM NONSPLIT PENDANT DOMINATION ENERGY OF A GRAPH - Swaroopa Rani N.C; B. Shanmukha (Utilitas Mathematica, 2025)
For a graph????, a subset ???? of ????(????) is called a nonsplit pendant dominating set if the induced graph